Effectiveness of Influenza Vaccination for Individuals with Chronic Obstructive Pulmonary Disease (COPD) in Low- and Middle-Income Countries. (2nd January 2016) - Lall, Dorothy; Cason, E.; Pasquel, F. J.; Ali, M. K.; Narayan, K. M. V.
Abstract : Chronic obstructive pulmonary disease (COPD) is one of the leading causes of death globally. In addition to the mortality associated with it, people with COPD experience significant morbidity, making this set of conditions a major public health concern. Infections caused by influenza virus are a preventable cause of morbidity and vaccination has been shown to be effective. The evidence of their benefit in persons with COPD mainly comes from high-income countries where influenza vaccination is used in routine practice, but little is known about the effectiveness, cost-effectiveness, and scalability of vaccination in low- and middle-income countries. We therefore systematically reviewed and present evidence related to vaccination against influenza in persons with COPD with a special focus on studies from low- and middle-income countries (LMICs). Available data from 19 studies suggest that the use of influenza vaccine in persons with COPD is beneficial, cost-effective, and may be relevant for low- and middle-income countries. Wider implementation of this intervention needs to take into account the health care delivery systems of LMICs and use of prevalent viral strains in vaccines to be most cost effective.